Regarding submission of terrazzo samples - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of terrazzo samples with cement of different colors and marble chips in different mixing ratios for BRACU new campus project.